Exciton-dominated optical response of ultra-narrow graphene nanoribbons - Denk, Richard; Hohage, Michael; Zeppenfeld, Peter; Cai, Jinming; Pignedoli, Carlo A.; Soede, Hajo; Fasel, Roman; Feng, Xinliang; Muellen, Klaus; Wang, Shudong; Prezzi, Deborah; Ferretti, Andrea; et al. (Nature Communications, 2014)
Narrow graphene nanoribbons exhibit substantial electronic bandgaps and optical properties fundamentally different from those of graphene. Unlike graphene - which shows a wavelength-independent absorbance for visible light - the electronic bandgap, and therefore the optical response, of graphene nanoribbons changes with ribbon width. Here we report on the optical properties of armchair graphene nanoribbons of width N=7 grown on metal surfaces. Reflectance difference spectroscopy in combination with ab initio calculations show that ultranarrow graphene nanoribbons have fully anisotropic optical properties dominated by excitonic effects that sensitively depend on the exact atomic structure. For N=7 armchair graphene nanoribbons, the optical response is dominated by absorption features at 2.1, 2.3 and 4.2 eV, in excellent agreement with ab initio calculations, which also reveal an absorbance of more than twice the one of graphene for linearly polarized light in the visible range of wavelengths. © 2014 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20